Youth Mental Health Peer Support Work: A Qualitative Study Exploring the Impacts and Challenges of Operating in a Peer Support Role - Calvert Tisdale; Nicole Snowdon; Julaine Allan; Leanne Hides; Philip Williams; Dominique de Andrade (MDPI AG, 2021)
Youth aged 16-24 years have the highest prevalence of mental illness in Australia, accounting for 26% of all mental illness. Youth mental health peer support work is a promising avenue of support for this population. However, limited research has examined impacts on those who provide youth mental health peer support work. We aimed to identify the benefits and challenges of working in a youth mental health peer support role. Semi-structured qualitative interviews with seven purposefully sampled peer workers from a national youth mental health organisation in Australia were conducted. The interviews were thematically analysed. Six key themes were identified: (1) personal growth, (2) interpersonal factors, (3) organisational factors, (4) boundaries, (5) role acknowledgement, and (6) challenging situations. Key supportive factors included financial reimbursement, training, support, and role-related flexibility. Identified challenges included lack of role acknowledgement, role-related stress, and boundaries. Operating within a youth mental health peer support role is perceived to have positive impacts on personal growth and interpersonal factors, enhanced through financial reimbursement, supervision, and role-related flexibility. Perspectives on the most effective form of role boundaries were diverse however their importance in addressing challenges was emphasised.